Cost-effectiveness of three screening strategies for atrial fibrillation in Sri Lanka: a decision-tree modelling analysis using community-based prevalence data - Shribavan, K.; Zainab, A.; Tiffany, E.G.; Sheron Antony, V.; Powsiga, U.; Chamira, K.; Balachandran, K.; Neil, T.; Krishnarajah, N.; Gregory, Y.H.L.; Mahesan, G.; Haniffa, R.; et al. (BMJ Global Health, 2026)
Introduction Early diagnosis and treatment of atrial fibrillation (AF) are crucial to reduce AF-related complications and associated healthcare costs. In low-resource settings, digital health technologies could help achieve this; however, costs of different screening strategies are key for policy change. Methods This decision-tree model representing the Sri Lankan public health system perspective used prevalence data from a community-based cross-sectional study of 10 000 individuals aged ≥50 years in Northern Province, Sri Lanka. Participants were screened for AF using AliveCor, a handheld single-lead ECG device. Three screening strategies (systematic, opportunistic and targeted) were compared against each other. The incremental cost-effectiveness ratio (ICER) is presented, representing the incremental total aggregated cost between screening strategies divided by the incremental number of new detected AF cases to generate a cost per additional new AF cases detected for a 1-year time horizon. Results Systematic screening detected 48 new AF cases, and the targeted screening detected 47. Systematic screening was more expensive (Sri Lankan rupees (Rs) 698 422; US$2123) for 10 000 screened individuals compared with targeted screening (Rs 492 002; US$1496) for 7780 screened individuals. Opportunistic screening was the cheapest strategy (Rs 360 617; US$1096) for screening 6556 individuals; however, only 30 new AF cases were identified. The ICER of targeted screening was lower compared with opportunistic screening (Rs 7729; US$23 per additional detected AF case) whereas the ICER of systematic screening compared with opportunistic screening was higher at Rs 18 767 (US$57) per detected AF case. When the systematic screening strategy was compared with targeted screening, the cost per additional detected AF case increased to Rs 206 420 ($628). Conclusion Targeted screening with AliveCor was the most cost-effective strategy. Systematic screening, while having similar effectiveness, was not cost-effective due to the high additional costs to detect just one further case. These findings support integrating targeted screening into Sri Lanka’s primary care pathways.